Desmids from Korea; 1. Desmidiaceae 1 (Micrasterias) - Han Soon Kim (Journal of Ecology and Environment)
The present study summarizes the occurrence, distribution and autecology of the genus Micrasterias Ralfs among desmids collected from several swamps, reservoirs, rivers and high land wetlands in South Korea from 2009 to 2013. In total 21 taxa of Micrasterias including three new species, Micrasterias spinosus sp. nov., M. jejuensis sp. nov. and M. koreanus sp. nov., were identified. In this study, photomicrographs of all of these are provided and briefly discussed with regard to their taxonomy, distribution and ecology within South Korea.